PERANCANGAN PERANGKAT LUNAK UNTUK PENGOLAHAN PENGHITUNGAN ANGKA KREDIT ( PAK ) KENAIKAN PANGKAT FUNGSIONAL DOSEN DAN LAPORAN KINERJA DOSEN ( LKD ) BERBASIS WEB Studi Kasus : (Institut Teknologi Padang) - Busran; Wike Erfi Yunita (ITP Press, 2016)
Application of numerical computation processing credit ( PAK ) the promotion of functional lecturers and faculty performance report (LKD) is an application that is designed to facilitate the process of promotion of functional lecturer at the Institute of Technology Padang. This application is designed to provide easy because the data is processed by using a database and does not need to repeatedly input, after the feasibility study ( feasibility study ) of data to be proces. When each element has a value of activities or different points so as to allow the occurrence of redundanciesof data.. Inputting the data include the data of education, teaching, research and Tridharma college. Applications designed in this study is based WEB. In the design of its web is built using the programming language PHP and uses a MySQL database.